The Role of Motivation in Mediating the Influence of Communication and Work Environment on Employee Performance at PT Agung Automall Sutomo, Pekanbaru City - Teguh Handoyo, Leonardus; Zulfitri, Zulfitri; Andriani, Dessy; Suleman Hsb, Mhd.; Suryatunnisak, Suryatunnisak (Journal of Engineering Science and Technology Management, 2025)
This study is a quantitative study that aims to determine the role of motivation in mediating the influence of communication and work environment on the performance of employees at PT Agung Automall Sutomo in Pekanbaru City. The population used in this study was all 125 employees of PT Agung Automall Pekanbaru. To determine the sample size for this study, the author used the Slovin formula, resulting in 96 employees as the sample, while the sampling method used was simple random sampling. The data analysis technique used was quantitative analysis using Structural Equation Modelling (SEM) with the Smart PLS program. The results of the study are as follows: 1) Communication and work environment have a positive and significant effect on employee motivation. 2) The work environment has a positive and significant effect on employee motivation. 3) Communication has a positive and significant effect on employee performance. 4) The work environment has a positive and significant effect on employee performance. 5) Motivation has a positive and significant effect on employee performance. 6) Communication affects employee performance through motivation. 7) The work environment affects employee performance through motivation.